2021
DOI: 10.3390/nu13124291
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors of Sarcopenia in Community-Dwelling Older Adults: A Systematic Review and Meta-Analysis

Abstract: (1) Background: To review the associated factors of sarcopenia in community-dwelling older adults. (2) Methods: PubMed, Embase, Web of Science, and four Chinese electronic databases were searched for observational studies that reported the associated factors of sarcopenia from inception to August 2021. Two researchers independently selected the literature, evaluated their quality, and extracted relevant data. The pooled odds ratio (OR) and its 95% confidence interval (CI) were calculated for each associated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
101
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 103 publications
8
101
1
2
Order By: Relevance
“…Osteopenia was present in 1402 evaluated subjects (44.0%), of which 53.1% (n = 750) were male (p < 0.001); osteoporosis was diagnosed in 1156 patients (39.9%), of which 990 were female (59.9%, p < 0.001), with higher prevalence in men (54.9% vs. 67.9% in women) [34]. None of the studies demonstrated an association of smoking with sarcopenia [33].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Osteopenia was present in 1402 evaluated subjects (44.0%), of which 53.1% (n = 750) were male (p < 0.001); osteoporosis was diagnosed in 1156 patients (39.9%), of which 990 were female (59.9%, p < 0.001), with higher prevalence in men (54.9% vs. 67.9% in women) [34]. None of the studies demonstrated an association of smoking with sarcopenia [33].…”
Section: Discussionmentioning
confidence: 95%
“…A meta-analysis performed on 68 studies (2021) that included a patient number of 98,502 looked at the association of socio-demographic, behavioral (nutrition, smoking, physical activity), and associated disease (including osteoporosis) factors with sarcopenia among the general population. Only six studies have reported decreased bone density and support that OP is a risk factor associated with sarcopenia in the elderly population [33]. Sarcopenia is significantly related to osteopenia and osteoporosis, as demonstrated in a study of 3077 volunteers over 65 years of age, regardless of associated pathology (Lee et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This study did not differentiate men and women during the risk factor analysis because chi-square test for the possible sarcopenia and sarcopenia prevalence of male and female showed that no difference between genders was found. It had been reported that gender was not a risk factor of the sarcopenia [ 50 , 51 ]. Indeed, our results may be attributed to relatively small sample size, the further work need to do in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of sarcopenia might reach up to 86.5% in adults depending on the definition used and the setting of evaluation, and is especially high in the older population [ 6 ]. This scenario deserves concern, given that the progression of sarcopenia is associated with the incidence of numerous negative events, including malnutrition, anorexia, physical inactivity, metabolic and osteoarticular disorders, cognitive impairment, falls, depressive symptoms, and death [ 7 , 8 ]. As such, sarcopenia is recognized as a public health problem and the identification of potential strategies to prevent its development and progression is a priority [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%